Menelaah Komunikasi Dakwah Komunitas Desa: Studi Kasus pada Majelis Taklim Syamsul Huda Tirtoyudo - Lutfa Putri Valentina (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
This research aims to identify communications elements in conveying This study aims to identify the elements of communication in the delivery of da’wah at Majelis Taklim Syamsul Huda by employing Edward T. Hall’s (1976) contextual communication theory and Wilbur Schramm’s (1954) communication model. This research adopts a descriptive qualitative approach using a case study method. Data were collected through observations, in-depth interviews with KH. Ali Mustofa and 15 active congregants, as well as documentation, and were analyzed using Miles and Huberman’s interactive model through the processes of data reduction, data display, and conclusion drawing. The findings show, first, that the sender of da’wah messages at Majelis Taklim Syamsul Huda predominantly applies a high-context communication style toward the rural community. Second, the persuasive messages delivered by the sender frequently employ explicit and verbal forms with strong local cultural values. Third, the level of contextuality in the preacher’s messages is also well received when conveyed through a low-context communication model.